ACTIVITIES OF SOCIALIZATION OF FOREIGNER REPORTING APPLICATION (APOA) V.2 BASED ON QR CODE BY IMMIGRATION OFFICE CLASS II BORDER CONTROL BELAWAN TO HOSPITALS AND LOCATIONS - Fazril Habib Manurung; W Wilonotomo (Polteknik Imigrasi, 2021)
The Foreigner Reporting Application (APOA) is an application created by the Directorate General of Immigration, and has now undergone a system update that previously could only be accessed through the website. The Foreigner Reporting Application (APOA) V.2 Based on QR Code is an improvement of the Foreigner Reporting Application (APOA) V.1 which has been previously implemented by guarantors, foreign sponsors, hotel and lodging parties. This APOA socialization activity was organized by the Immigration Office Class II TPI Belawan together with the Immigration Polytechnic cadets to provide information related to the development of the system in the Foreigner Reporting Application (APOA) V.2, making it easier for the public to provide information to relevant immigration officers regarding foreigners who in the work area of the Immigration Office Class II TPI Belawan. In addition, it can minimize the spread of the Covid 19 virus due to the reduced movement of people who will provide information regarding foreigners to the Class II Immigration Office of TPI Belawan.